Regulations for trade between Cossacks and highlanders in the first half of the 19th century - Kseniya Y Sukhomlinova (RUDN Journal of Russian History, 2018)
The resettlement of Kuban Cossacks and the exploration of new territories in the late 18th and early 19th centuries were fraught with difficulties. While the Cossacks’ main function was the establishment of a cordon line and the protection of the Russian Empire’s borders, they were also given the opportunity to build new and mutually beneficial trade relations with the population groups of the near-by Caucasus. The establishment of exchange trade yards on the border required regulations and documentation. The article discusses the functioning of the exchange trade yards in the Kuban region in the 19th century, as well as the main measures taken by the government of the Russian Empire and the administration of the Black Sea Cossack Host for developing trade between the Cossacks and the Caucasian population. The author analyzes the history of the trade yards from their foundation in the early 19th century to their abolition in the 1850s; equally discussed are the problems which the Cossacks and Caucasians faced in the process of exchanging goods, and the measures taken by officials to solve these problems. The focus is on a number of archival documents which regulated the process of trading, in particular tariffs on basic goods and rules for bartering with highlanders.